Modern witchcraft in suburban Australia: how and what witches learn - Smith, Zena Diane (Curtin University, 2010)
Existing anthropological research and discussion related to contemporary Wiccan and Witchcraft practice is growing and indeed has been explored by anthropologists and other writers from the northern and southern hemispheres. However, there has been limited discourse on how and what Western Australian Wiccans and Witches learn. This ethnographic research fills that gap by exploring, in two separate sections, how Wiccans and Witches have developed relevant skills in a social learning structure and what ritual practice they have learnt as a result. The thesis proposes that the current theories of learning and ritual fail to adequately describe the social processes and outcomes observed.In the first section, focusing on how the participants learn, I argue that cognitive, behavioural and humanist learning theories as well as the most relevant social learning theory, Communities of Practice, fail to explain adequately the holistic learning processes with which the Wiccans and Witches are engaged. Instead I propose a new and complementary theory of learning that I identify as 'Whole Person’ theory that more effectively describes the holistic and intuitive nature of learning the research participants undertook.In the second section I go further to show that the existing theories of ritual fail to explore and consider ritual as a product or outcome of learning and instead focus heavily on ritual either as a process contributing to and reflecting the social order in which it takes place or they describe the structure of ritual. This research shows that ritual can be both a process of a social group as well as a product and an end result of learning and social interaction. The ethnographic materials presented extend our understanding of both learning and ritual.